Understanding and responding to the regional perceptions of the global economic crisis: towards the ”low-tech” knowledge-based approach - ALFIREVIC, Niksa; PAVICIC, Jurica; ZNIDAR, Kresimir (Annals of Spiru Haret University. Economic Series, 2010)
In this paper, authors apply the ’sense-and-respond’ model to understanding and modeling reactions of customers in the wider South-East European (SEE) region to the actual economic crisis. As results of the previous research indicate that the role of contemporary knowledge-based tools can serve as a complement, rather as a replacement for the ’traditional’ research methodology, the role of universities and other knowledge providers to the business community in responding to the economic crisis is also critically examined. The paper suggests that development and the use of a modified ’sense-and-response’ model at the industry/cluster level could assist all economic and social actors in relieving the consequences of the economic crisis/recession, as well as affirm the role of the university in the process[1].